Follicular dynamics, hormonal and biochemical profile across seasons in buffaloes - JEROME, A; SRIVASTAVA, S K; SHARMA, R K; SARKAR, S K; KUMAR, R (The Indian Journal of Animal Sciences, 2017)
The present study was conducted to deduce the alteration in follicular dynamics, hormonal and biochemical profile across seasons in buffaloes. In this study, 14 cyclic buffaloes were selected for assessing the follicular dynamics, hormonal and biochemical profile, 7 each during summer and winter. Higher ambient temperature was observed in summer as compared to winter. Nonsignificant difference across seasons with respect to growth rate of follicles and duration of follicular waves was observed. Serum progesterone (P4) showed no significant difference across seasons but differed significantly with respect to days of the estrous cycle in both seasons. Cortisol level did differ significantly from day 4 to day 16 of estrous cycle across seasons. Follicular hormones, viz. estradiol and P4 were significantly higher irrespective of seasons as compared to peripheral level. Follicular biochemical parameters, viz. cholesterol, total protein significantly differed between serum and follicular fluid during summer. Similarly during winter, follicular glucose was higher as compared to serum. In conclusion, season has a significant effect on peripheral cortisol with nonsignificant alterations in follicular dynamics, follicular hormones (E2 and P4) and biochemical milieu across seasons in cyclic buffaloes.